Educação e alimentação: representações de discentes de uma escola pública de tempo integral do Estado do Ceará sobre alimentação - Nascimento, André Araújo do (2023)
The dissertation investigates the representations of first-year high school students in a full-time public school in Ceará, Brazil, regarding food and healthy eating. It examines daily practices marked by consumerism, highlighting its influence on the construction of sociocultural values. The intersection of education and nutrition is crucial for promoting healthy habits among young people, considering the impact on families and communities. Using Social Representations Theory as a theoretical and methodological framework, drawing on the studies of Moscovici (1978, 2007) and Jodelet (2001, 2005), the research addresses historical and sociological elements, emphasizing the relationship between healthy eating, physical appearance, and the school context. Additionally, it incorporates reference to Bezerra's (2002) thesis titled "Eating at school – meaning and implications." The sociocultural dimension of food is highlighted, exploring the Framework for Food and Nutritional Education (EAN) proposed by Bezerra (2018). The case study methodology, involving questionnaires and interviews, maps students' representations, identifies attributed meanings, and characterizes eating practices. The findings conclude that students' eating practices are crucial for understanding the link between perceptions of food and daily habits, revealing contradictions, especially regarding the concept of healthy eating. In school, students maintain regular eating habits governed by rules and schedules, while at home, there is a lack of regulation, particularly regarding unhealthy foods. The connection between media, food, and body stands out, emphasizing the direct influence on healthy eating. The research indicates a lack of effective educational initiatives in the school to promote healthy eating habits, with a negative index, pointing to sporadic lectures by the Ministry of Education's nutritionists and few mentions by teachers in specific subjects.